A qualitative exploration of 14 to 17-year old adolescents' views of early and preventative mental health support in schools. (22nd December 2020) - Spencer, Liam; McGovern, Ruth; Kaner, Eileen
Abstract: Background: Preventative interventions may be effective in reducing and preventing symptoms of mental ill health in children and young people. However, there is a paucity of research in this area that explores the views of young people. This paper reports on a qualitative study to inform the future development of attractive and appropriate early and preventative school-based mental health interventions. Methods: Semi-structured interviews were conducted with a purposive sample of 12 young people aged 14–17 in North East England. Interviews were audio-recorded, transcribed, anonymised and analysed following a thematic approach. Results: Four key themes were identified, relevant to those providing, designing and commissioning early and preventative mental health interventions in schools: 'mental health literacy', 'risk factors for wellbeing decline', 'experience of school-based support' and 'recommendations for future support'. Conclusions: Young people have varying levels of mental health literacy, but are able to identify academic stress, bullying and the transition from primary to secondary school as leading causes of worry. Young people want more regular and in-depth mental health education, tailored levels of support in school and improved training for teachers.